The in-between bookstore : a novel - Underhill, Edward (Avon Books, 2025)
"A whimsical and healing novel about a trans man in New York who-almost 30, laid off, broke-moves back to his small Illinois hometown, walks into the bookstore he worked at in high school. . . and slips through time to come face-to-face with his pre-transition, teenage self"--